Honokiol and magnolol - comparison of inhibitory activity of enzymes involved in carbohydrate and lipid metabolism and antioxidant properties in in vitro studies - Katarzyna Szałabska-Rąpała; Weronika Borymska; Maria Zych; Ilona Kaczmarczyk-Żebrowska (Polskie Towarzystwo Farmaceutyczne, 2023)
Oxidative stress is the basis of the pathogenesis of diabetes, obesity and their complications. Under its influence, free radicals that have not been neutralized or removed from the cell environment lead to damage to cellular macromolecules - carbohydrates, lipids and proteins. Honokiol and magnolol are neolignans derived from magnolia bark, which may be promising candidates in the fight against oxidative stress-related diseases. The aim of this study was to evaluate the antioxidant potential of structural isomers - honokiol and magnolol - in vitro, taking into account their effect on radicals and the potential possibility of protecting biomolecules against oxidative damage, as well as to analyze their capability to inhibit the activity of enzymes associated with carbohydrate and lipid metabolism. The abilities of neolignans to neutralize ABTS and DPPH radicals and also to prevent the formation of markers of oxidative damage - advanced oxidation protein products and thiobarbituric acid reactive substances were tested. The inhibitory properties of the compounds against the activity of enzymes (α-amylase, α-glucosidase, lipase) were also examined. The conducted analyzes indicate that in vitro honokiol possesses much better antioxidant properties and inhibits enzymes related to carbohydrate metabolism than magnolol. It neutralized model radicals and prevented oxidative damages almost as effectively as the reference compounds, with even better ability to inhibit enzymes involved in carbohydrate metabolism. None of the neolignans significantlly affected the reduction of lipase activity. The effectiveness of honokiol and magnolol as free radical scavengers and α-glucosidase and α-amylase inhibitors requires further confirmation in in vivo models.